Прогнозування прибутковості підприємства ресторанного бізнесу та чинників впливу на його фінансові показники - Шапран, Євген Миколайович; Сергієнко, Олена Андріанівна; Білоцерківський, Олександр Борисович (ВД "Гельветика", 2020)
У роботі розроблено комплекс моделей формування стратегії розвитку підприємств ресторанного бізнесу, що полягає у побудові економетричних моделей прогнозування прибутковості підприємства, які дають змогу оцінити поточний та перспективний стан діяльності підприємства. Для декомпозиції часового ряду, що характеризує прибуток підприємства, побудовано адитивну та мультиплікативну моделі складників, перевірено їх адекватність на основі показника середньої абсолютної відсоткової похибки. Доведено, що саме тренд-сезонна модель адекватно описує досліджуваний динамічний процес та найкраще характеризує початкові дані. Здійснено прогнозування показників прибутковості з урахуванням компонент сезонності та циклічності. Побудовано адекватну множинну економетричну модель залежності прибутку від чинників фінансово-економічної діяльності. Визначено найбільш суттєві чинники впливу на фінансові показники підприємства. Побудований комплекс моделей може бути використаний для прогнозування прибутковості як підприємств ресторанного бізнесу, так і широкого спектру підприємств сфери послуг та визначення чинників впливу на фінансові показники для підвищення ефективності системи управління шляхом оптимізації та автоматизації бізнес-процесів.

The restaurant business is one of the most profitable sectors of the economy, which is intensively developing and plays an important role in ensuring the sustainable socio-economic development of many countries and regions. For businesses of the service industry, it’s necessary to implement modern management tools, such as economic and mathematical apparatus for evaluation, analysis and forecasting, as the increased competition in the market of hotel and restaurant business requires constant and constructive changes. The purpose of the article is to develop a set of interrelated models of forming a strategy for the development of restaurant business enterprises. This set includes constructing adequate models for forecasting the profitability of the enterprise, taking into account the specificity of the profit formation processes, which will allow to evaluate the current state of the enterprise activity and to identify weaknesses. Also, it enables to forecast profitability indicators taking into account development trends and seasonality, as well as to identify significant factors influencing on the enterprise financial performance. As the result, this will allow to develop a set of programs and strategies for competitive development. For the decomposition of the time series that characterizes the profit of the enterprise, additive and multiplicative models are constructed; their adequacy is checked on the basis of the mean absolute percentage error. Profitability forecasting based on seasonality components is carried out. An adequate multiple linear econometric model of profit dependence on financial and economic activity factors is obtained. Indicators and variables included in the regression equation were tested for multicollinearity. The most significant factors influencing on the enterprise profit are determined. They include the company’s total net revenue, other operating revenues of the complex, cost of goods, costs of marketing and other operational costs. The built-in model complex can be used to predict the profitability of both restaurant business and a wide range of service businesses. Also, it enables to identify factors influencing on financial performance for improving the effectiveness of the management system by optimizing and automating business processes.
Forecasting the profitability of the restaurant business and the factors influencing on its financial indicators
Keywords: ресторанний бізнес; прибутковість; тренд-сезонна модель; економетрична модель; фінансові показники; адекватність; restaurant business; profitability; trend seasonal model; econometric model; financial indicators; adequacy